Developing a Process Development-based Instructional Model to Cultivate the Acquisition of Poetry Recitation Competence - Fatonah, Umi; Safitri, Ani; Maisalinia, Ria; Rahman, Fadillah Nuzulul; Rahmawanti, Movi Riana (Akademika : Jurnal Teknologi Pendidikan, 2025)
The integration of language and literary skills within vocational education often presents a pedagogical challenge, particularly in technical majors where curriculum emphasis leans heavily toward practical, non-literary subjects. This study addresses the need for an effective, engaging instructional approach to foster poetry reading and recitation competence among students in a vocational setting. The research was conducted by combining two instructional models—namely, Discovery Learning and Problem-Based Learning—to create the resulting Process Development learning model. The research subjects were 26 students from the 10th-grade TKJ (Computer and Network Engineering) class at SMK Informatika Pesat Bogor. This study employed Research and Development (R&D), utilizing a qualitative research methodology. The research instruments included observation and interviews. The findings indicate that the developed Process Development learning model for poetry reading skills is quite good and is effective in motivating and engaging students during the language development process. The feasibility of the Process Development learning model shows that it is appropriate for use in increasing students' self-confidence to actively explore concepts related to poetry reading skills